PALYNOLOGICAL STUDY OF phlomis L. (LABIATAE) SPP.GROWN IN IRAQ AND ITS TAXONOMIC USES. - Al-Omar, M.; Al-Najjar, N. (Iraqi Journal of Science, 2025)
Pollen of Phlomis spp. grown wildly in Iraq has been investigated for the firsttime, as a part of comparative study for the species of this genus.Description of these pollen were important in diagnosis of this spp., the studyshowed that pollen were isopolar and a single pollen is tricolpate, with reticulatesurface, and spherical -subspherical, in polar view, and almost ellipsoid to shortlyellipsoid in equatorial view, but it was spherical in P. oliveri Bth.;The longest axis of the pollen is ٤٨ um, thus all the species included in present studywere of medium size. Pollen of P.oliveri was the smallest in size, while pollen ofP.rigida Labill was the biggest.There is a table for result, also figures and diagrams for illustration